2021
DOI: 10.3390/ijms22031273
|View full text |Cite
|
Sign up to set email alerts
|

The Cholinergic System, the Adrenergic System and the Neuropathology of Alzheimer’s Disease

Abstract: Neurodegenerative diseases are a major public health problem worldwide with a wide spectrum of symptoms and physiological effects. It has been long reported that the dysregulation of the cholinergic system and the adrenergic system are linked to the etiology of Alzheimer’s disease. Cholinergic neurons are widely distributed in brain regions that play a role in cognitive functions and normal cholinergic signaling related to learning and memory is dependent on acetylcholine. The Locus Coeruleus norepinephrine (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 141 publications
0
50
0
Order By: Relevance
“…Disturbances in cholinergic transmission are characteristic of the late stages of neurodegeneration. For example, decreased ChAT and AChE activity was observed in AD, and the use of AChE inhibitors improved cognition in these patients, confirming the role of diminished ACh levels in the pathogenesis of AD [ 79 , 80 , 81 ].…”
Section: Pathophysiology Of Alzheimer’s Diseasementioning
confidence: 74%
See 2 more Smart Citations
“…Disturbances in cholinergic transmission are characteristic of the late stages of neurodegeneration. For example, decreased ChAT and AChE activity was observed in AD, and the use of AChE inhibitors improved cognition in these patients, confirming the role of diminished ACh levels in the pathogenesis of AD [ 79 , 80 , 81 ].…”
Section: Pathophysiology Of Alzheimer’s Diseasementioning
confidence: 74%
“…Additionally, AD patients have a reduced number of nAChR and mAChR receptors. The most important receptor types in AD among nAChRs seem to be α7 nAChR and α4β2 nAChRs, which have been found to be lessened in AD patients [ 79 ] (Bekdash, 2021). Stimulation of α7 nAChR in microglia leads to the activation of an anti-inflammatory response and to regulation of oxidative stress.…”
Section: Pathophysiology Of Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The strong involvement of the cholinergic circuits in age-related brain functional deterioration has led to the development of cholinergic hypothesis of geriatric cognitive impairments [18,[70][71][72][73]. In normal aged brains, loss of cholinergic neurons, depletion of ACh, reduced ChAT activity, and declines in the densities of muscarinic and nicotinic ACh receptors have been reported [12,13,18,19,58,72,73]. Based on positron emission tomography, Albin et al [74] reported region-specific declines in VAChT binding sites in the cortex and striatum in the aged brain.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of AD is associated with changes in synaptic signaling, loss of synapses, and neuron degeneration [ 3 ]. It has long been reported that the dysregulation of the cholinergic system in the basal forebrain, a master regulator of executive and mnemonic functions, is linked to memory loss/cognitive decline in AD [ 4 , 5 ]. The cortical cholinergic denervation remains one of the earliest, most severe, and most consistent transmitter changes observed during AD progression, which led to the formulation of the “cholinergic hypothesis” [ 6 ].…”
Section: Introductionmentioning
confidence: 99%